A Guide to science and index to the Life science library (New York : Rhett Austell, 1966)
A survey of the history of science and picture essays describing individual fields:Smallest known objects, the subnuclear particles of the atom, successive essays, take up objects of increasing size, such as animals and human beings, and largest known objects, stars and galaxies.
Include index.
Keywords: Life science library -- Indexes